Polyanion Materials for K-Ion Batteries - S. Kalanur, Shankara; Seo, Hyungtak; Kalanoor, Basanth S. (Potassium-Ion Batteries: Materials and Applications, 2020)
Potassium-ion based battery is the emerging electrochemical energy storage technology of the future, owing to the abundance and accessibility of potassiumcontaining materials. Mainly, the utilization of polyanion based cathodes in potassium-ion batteries is found to pose some unique advantages over the conventional cathode materials such as the introduction of inductive effect due to the increased electronegativity of anions, provide high de-potassiation potentials, high thermal stability as well as facile potassium ion diffusion pathways due to the unique three dimensional framework. In this chapter, the polyanion materials employed in the recent potassium-ion battery applications are discussed. Mainly, the contribution of polyanion materials such as fluorosulfates, phosphates, double phosphates, vanadyl phosphates, and vanadyl flourophosphates, are investigated. Despite significant research on potassium-ion batteries, the contribution of wide range of polyanions is limited, unlike in the other alkali ion-based battery system. Hence, more substantial research contribution is essential to explore wide range of polyanion materials focusing on environmentally benign synthesis protocol, morphology, stability and flexible crystallographic framework. Importantly, the future research direction should include the development of efficient polyanion material literature with the establishment of the large-scale commercialization methodology.
Keywords: Double phosphates; Fluoro-phosphates; Fluorosulphate; Ion batteries; K-ion battery; Polyanions; Potassium ions; Vanadyl; Vanadyl fluorophosphate; Vanadyl phosphate; Cathodes; Double phosphates; Fluorosulfates; K-ion batteries; Phosphates; Polyanion; Vanadyl fluorophosphates; Vanadyl phosphates